Mapping the Scientific Landscape of Integrated Marketing Communication and Brand: A Bibliometric Analysis (1996–2023) - Yudho Novandhika Putra; Lissa Rosdiana Noer (Direktorat Riset dan Pengabdian Kepada Masyarakat, Institut Teknologi Sepuluh Nopember, 2025)
Purpose – This study aims to map and analyze the scientific development of Integrated Marketing Communication (IMC) research and its relationship with brand equity within the fields of business, management, and accounting. Methodology – A bibliometric analysis was conducted using 175 peer-reviewed articles indexed in the Scopus database published between 1996 and 2023. The study applies performance analysis and science mapping techniques, utilizing VOSviewer to identify influential authors, documents, journals, and thematic research clusters in the IMC–branding literature. Findings – The results reveal that Keller (2009) and Schultz emerge as the most influential contributors in the IMC research landscape. The thematic mapping indicates that recent research trends emphasize the integration of social media and message consistency as critical elements of effective IMC strategies in building brand equity. The analysis also shows a growing interdisciplinary orientation and increasing academic interest in digital communication channels. Originality – This study offers a comprehensive bibliometric overview of IMC and branding research over nearly three decades, highlighting intellectual structures, influential contributors, and emerging themes. It contributes to the literature by systematically synthesizing the evolution of IMC scholarship and identifying future research directions relevant to both academics and practitioners. Practical implications – The findings provide valuable insights for marketing practitioners and brand managers in designing cohesive IMC strategies, particularly in leveraging digital and social media platforms to enhance brand equity through consistent messaging.